URGENSI NILAI PANCASILA PADA GENERASI MILLENIAL - Mei Nur Rusmiati; Dinie Anggraeni Dewi (Universitas Muhammadiyah Enrekang, 2021)
This paper aims to make people better understand the urgency of the value of Pancasila in social and state life. Moreover, at this time the millennial generation has very far left the values ​​of Pancasila. Therefore, it is necessary to have encouragement again so that the urgency of the value of Pancasila is not increasingly abandoned. This study uses a qualitative method with a descriptive approach, namely by means of discussion theory obtained from the results of literature studies and also various existing sources, one of which is a journal. With the erosion of people's understanding of the value of Pancasila, the authors intend to provide a re-understanding of the value of Pancasila which is starting to disappear from the personality of Indonesian society. As well as explaining the actions of the millennial generation that are against the values ​​of Pancasila. With this, it is hoped that it will be able to make people aware of the importance of the value of Pancasila which is not only remembered, but also must be implemented in everyday life.